Physical properties of diamond and sapphire - Aggarwal, R. L.
"Focusing on the physical properties of diamond and sapphire, this monograph describes essential details on crystal structure and growth, mechanical properties, thermal properties, optical properties, light scattering of diamond and sapphire crystals, and sapphire lasers. Mechanical properties include hardness, tensile strength, compressive strength, and Young's modulus. Thermal properties include thermal expansion, specific heat, and thermal conductivity. Optical properties of diamond and sapphire include transmission, refractive index, and absorption. Light scattering includes Raman scattering and Brillouin scattering. Sapphire lasers include chromium-doped and titanium-doped lasers"--